Free the Children as a 'new secular spiritual movement': a case study on the conceptual boundaries between 'spirituality', 'the sacred', and 'new religious movements'. Issue 2 (3rd July 2017) - Mosurinjohn, Sharday; Funnell-Kononuk, Emma
ABSTRACT: The movement under study, Free the Children (FtC), is a youth empowerment organization that was founded in 1995 by a Canadian teenager, who, twenty years on, remains its leader today. Though it does not define itself as either a religion or an alternative to religion, it frequently uses the language of 'spirituality'. Moreover, it meets all five criteria proposed by Lorne Dawson [2006. "New Religious Movements." In The Blackwell Companion to the Study of Religion, edited by Robert A. Segal, 269–284. Malden: Blackwell, 374] to define a new religious movement (NRM). It likewise demonstrates a valuation of certain principles (belonging, community, compassion, and caring) as set apart and inviolable: what Kim Knott [2013. "The Secular Sacred: In-between or Both/And?" In Social Identities between the Sacred and the Secular, edited by Abby Day, Giselle Vincett and Christopher R. Cotter, 145–160. Farnham: Ashgate] characterizes as 'the secular sacred'. Trying to situate FtC in the post-war 'seeking culture' in which so many NRMs and 'alternative spiritualities' arose [Clarke, Peter B. 2006. New Religions in Global Perspective: A Study of Religious Change in the Modern World . New York: Routledge] reveals a major conceptual problem: 'spirituality', 'the sacred', and 'NRMs' have been operationally defined in many pieces of religious studies literature in relation to 'religion' and other terms, but never systematically in relation to each other. This is what our project proposes to do, provisionally offering the term 'new secular spiritual movement' (NSSM) as a heuristic.